Physical and optical properties of aerosols over an urban location in Spain: seasonal and diurnal variability - H. Lyamani; F. J. Olmo; L. Alados-Arboledas (Atmospheric Chemistry and Physics, 2010)
Measurements of aerosol optical properties and aerosol number size distribution obtained during the period from December 2005 to November 2007 at Granada, an urban site in south-eastern Spain, are analyzed. Large variations of the measured variables have been found, and related to variations in emissions sources and meteorological conditions. High values of aerosol absorption and scattering coefficients are obtained during winter and low values are measured during summer. This seasonal pattern in the surface aerosol optical properties is opposite to the seasonal cycle showed by columnar aerosol optical depth. The differences in the seasonal features of the surface and column-integrated data are related to seasonal variations in the aerosol vertical distribution, aerosol sources and boundary layer height. In winter the number density of "fine" particles (0.5<particle diameter<1 μm) is significantly larger than in summer while the number density of "coarse" particles (1<particle diameter<20 μm) is slightly larger during summer and spring than during winter and autumn. The scattering Angström exponent, αs, presents an evident seasonal cycle with values of 1.8±0.2, 1.6±0.3, 1.3±0.3 and 1.4±0.3 in winter, spring, summer and autumn, respectively. This suggests the presence of a large fraction of submicron particles at the site, especially during winter. The aerosols measured in this study contain a large fraction of absorbing material as indicated by the average single-scattering albedo that has values of 0.65±0.07, 0.66±0.06, 0.70±0.06 and 0.73±0.06 in autumn, winter, spring and summer, respectively. The aerosol scattering albedo obtained in the surface boundary layer of Granada is below the critical value of 0.86 that determines the shift from cooling to warming. These results put in evidence the need of efforts to reduce absorbing particles (black carbon) emissions to avoid the possible warming that would result from the reductions of the cooling aerosols only. The aerosol absorption and scattering coefficients present a clear diurnal pattern, in all seasons, with two local maxima, one early in the morning and the second one in the evening. This diurnal cycle is mainly attributed to the diurnal evolution of atmospheric boundary layer and local anthropogenic activities.